The Effect Of Leptospirosis Health Intervention Module On Knowledge And Attitudes In Informal Sector Workers In Semarang City (Intervention Study In The Working Area Of Kedungmundu Health Center Semarang) - Apriani Tiaraningtias; Dwi Sutiningsih; Onny Setiani (Syntax Corporation Indonesia, 2023)
Leptospirosis is a zoonotic disease caused by the bacterial genus Leptospira, and a worldwide public health problem caused by climatic and environmental conditions. The incidence of lepotopsirosis in Central Java has always increased in the last two years, namely in 2021 there were 285 cases with a death rate of 44 people (CFR: 16.60%) cases, in 2022 there were 503 cases with a death rate of 70 cases (CFR: 13.32 %). The aim of this research is to analyze the differences before and after administering the leptospirosis health intervention module on knowledge, attitudes, beliefs and practices among informal sector workers in Semarang City (intervention study in the Kedungmundu Semarang health center working area). The research design used a control intervention study with a sample of 45 interventions and 45 controls. The intervention and control groups were determined based on the results of leptospirosis cases found in the working area of the Kedungmundu Community Health Center, Semarang City in 2020 - 2023. Data analysis was carried out univariately, bivariately using the Wilcoxon test and the Mann-Withney test. The results showed that knowledge (p<0.001), attitude (p=0.001). The mean differences between the intervention and control groups were 62.11 and 28.89 for knowledge, 63.86 and 27.14 for attitudes. The Leptospirosis Health Intervention Program is an effective health program, an educational tool to increase awareness and preventive behavior among at-risk groups such as informal sector workers, farmers and livestock breeders